A Perspective on Recent Advances in 2D Stanene Nanosheets. Issue 18 (4th August 2019) - Sahoo, Sumanta Kumar; Wei, Kung‐Hwa
Abstract: Advancements in 2D nanomaterials have been impacting a wide range of technology‐driven applications. Here, the authors highlight stanene, a material that comprises a monolayer of elemental tin atoms, as a new addition to the monoelemental 2D family. Recent successes in the experimental realization of stanene in supported heterostructures and in free‐standing form have expanded interest in exploring and unlocking its potential applications, as predicted from advanced theoretical calculations. Stanene exhibits several remarkable features, including a large spin–orbit gap (allowing room‐temperature electronics based on the quantum spin Hall effect), topological superconductivity, quantum anomalous Hall behavior, giant magnetoresistance, and efficient thermoelectricity. Research into stanene and stanene‐based 2D materials, both experimentally and theoretically, is suggesting immense potential for future quantum‐based electronics systems. Here, the fundamental features of stanene, progress in its synthesis, and future perspectives are discussed. Abstract : Stanene is a new member of the 2D nanomaterials family, composed of a monoelemental atomic layer of tin atoms. The research progress in fundamental features, advanced quantum behaviors such as topological superconducting phenomena, various synthesis process, and future perspectives of the emerging 2D nanomaterial are reviewed.